(untitled) (Research, Society and Development, 2021)
Introduction: Diastemas are found among the main aesthetic ones of patients and can be classified as extra spaces, located between the most important ones, caused by differences in the size of the two faces, absence of differences, disproportion of faces in the upper arch and lower, deleterious habits and several others. factors. The search for conservative treatments allowed the development of increasingly improved resins, which aim to establish restorations with satisfactory aesthetics in a shorter time of work, without the need for greater wear, preserving the dental structure. Objectives: To present a clinical case where aesthetics can be reestablished in previous diastema with the use of direct resins and wetting agents, avoiding further wear, restoring function and self-esteem to the patient. Description of the case: A photographic protocol was carried out, whitening in the office and at home, followed by a diagnostic wax-up, assembly in an articulator, revision of guides, elaboration of a silicone matrix to obtain the incisal, followed by a circle of the diastema with direct resins and a thin surface layer with a wetting agent. Final considerations: The composite resin has proven to be an excellent alternative when it correctly uses a trained professional who understands the aesthetic and psychological principles of your patient. The use of a humectant agent associated with composite resin provided the success of the restorative treatment, facilitating the manipulation of the resin and, consequently, the anatomy, surpassing the patient’s expectations, restoring the aesthetics of their clients, thus increasing their self-esteem.